2019
DOI: 10.3390/nu11010091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of β-Fructans Fiber on Bowel Function: A Systematic Review and Meta-Analysis

Abstract: The aim of this systematic review and meta-analysis was to assess the effects of β-fructan supplementation on bowel function in healthy volunteers and patients. The search process was based on the selection of publications listed in the Pubmed and EUPMC database until December 2017, plus two unpublished studies, to identify studies evaluating the impact of β-fructans on bowel movement and stool parameters. Forty-seven publications were selected for inclusion. Primary parameter was frequency of bowel movements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 76 publications
1
26
0
5
Order By: Relevance
“…Such selective effects are confirmed by the newer 16S rRNA-based high-throughput sequencing methods, as shown in this review. Initially inulins were valued for improving digestive health or bowel habit, that has been more recently substantiated by a systematic review (De Vries et al, 2019). Importantly there is an increasing evidence for inulins' role in glucose homeostasis relevant against type 2 diabetes and obesity, amongst several other benefits (Canfora et al, 2015;Koh et al, 2016;Liu et al, 2017b;Slavin, 2013;Stephen et al, 2017;Van de Wouw et al, 2018;Van der Beek et al, 2018).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Such selective effects are confirmed by the newer 16S rRNA-based high-throughput sequencing methods, as shown in this review. Initially inulins were valued for improving digestive health or bowel habit, that has been more recently substantiated by a systematic review (De Vries et al, 2019). Importantly there is an increasing evidence for inulins' role in glucose homeostasis relevant against type 2 diabetes and obesity, amongst several other benefits (Canfora et al, 2015;Koh et al, 2016;Liu et al, 2017b;Slavin, 2013;Stephen et al, 2017;Van de Wouw et al, 2018;Van der Beek et al, 2018).…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Circulating plasma propionate seems to be the most reflective of its respective fecal concentrations, whilst fecal acetate and butyrate were not related to their respective circulating concentrations. In line, previous literature reports that SCFA flux into the circulation and uptake in peripheral tissues rather than microbial SCFA production per se is of importance for metabolic health [26][27][28]. Our data emphasize the need to measure circulating SCFA in human prebiotic/probiotic intervention studies as a biomarker/mediator of effects on host metabolism.…”
Section: Discussionsupporting
confidence: 89%
“…In the overweight or obese state, GE rate has been reported to be faster, similar or delayed compared to lean individuals [25,26]. However, a recent, large-scale cross-sectional analysis reported faster GE rates measured via scintigraphy and reduced fasting plasma PYY concentrations in overweight and obese compared to lean adults [27]. Therefore, it is intriguing to speculate that accelerated GE in obesity may lead to rapid postprandial blood glucose peak, thus imposing a constant challenge to postprandial glucose homeostasis.…”
Section: Gastric Emptying and Blood Glucose Homeostasismentioning
confidence: 98%
See 1 more Smart Citation
“…Since FODMAPs are a major energy source for colonic microbes, bacterial loads can be expected to vary with FODMAP intake. Such effects are indeed noted in healthy individuals, where high fiber diets or prebiotic supplementation are associated with higher bacterial densities and/or higher fecal volumes [73][74][75][76][77], and low FODMAP diets are associated with reduced bacterial densities (but not necessarily colonic volumes) compared to habitual or comparator diets [22,52]. Here, only Halmos et al and Staudacher et al reported data on total bacterial densities, measured as the number of copies of the 16S rRNA gene by qPCR per gram of feces, in Crohn's disease and IBS patients, respectively.…”
Section: Resultsmentioning
confidence: 91%